ANALISIS PENGARUH NIM, BOPO, LDR, DAN NPL TERHADAP PROFITABILITAS (Studi Kasus Pada Bank Umum Yang Listed Di Bursa Efek Indonesia Periode 2014-2018) - Wulandari Danu Lestari; R. Gunawan Setianegara (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This research aims to determine the effect of Net Interest Margin (NIM), Operation Expenses to Operations Income (BOPO), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL) toward Profitability (Case Study on the Commercial Banks that Listed in Indonesia Stock Exchange period 2014-2018).In this research the sampling technique used was purposive sampling technique and managed to obtained 13 banks. Secondary data used were obtained from financial reports published from the official website of the Otoritas Jasa Keuangan (OJK). Methods of data analysis used in this study is the analysis of multiple linear regression with a level of significance of 5%.The results showed that the variables NIM, BOPO, LDR, and NPL simultaneously have significant effect to Profitability. Based on the t-test results it can be concluded that the variables NIM and BOPO have significant effect while LDR, and NPL have not significant effect to Profitability. The results obtained by multiple linear regression analysis Adjusted R2 of 0.976, this shows that the contribution of independent variables in explaining the dependent variable is 97,6% and the remaining is explained by other variables that are not examined.